Perak and the Malays "sārong" and "krīs - McNair, John Frederick Adolphus 1828-1910 (Silverfish Malaysian classics, 2019)
This Malayan State, it will be remembered, came into public notice in 1875-76, through the murder there of the British Resident, and the despatch by our Government of a combined naval and military force to exact satisfaction for the outrage. As I accompanied the Governor of the Straits Settlements on his progress through the country just prior to the disturbances, and was also with the force subsequently sent there, I enjoyed exceptional opportunities for observation, of which I availed myself, in making the notes which have since been embodied in this work.